Counting the cost of agricultural support on nature, climate, nutrition, health and equity - Glauber, Joseph W.; Laborde Debucquet, David (Food and Agricultural Organization of the United Nations, 2021)
KEY MESSAGES Global support to farmers is projected to reach almost USD 1.8 trillion in 2030. About 73 percent of this (USD 1.3 trillion) will be in the form of border measures, which affect trade and domestic market prices. The remaining 27 percent (USD 475 billion) will be in the form of fiscal subsidies to agricultural producers. Agricultural support that is harmful to nature, climate, nutrition and health should be removed or reduced. But to ensure a beneficial outcome overall, any fiscal savings should be repurposed towards agricultural support that is healthier, more sustainable and equitable, while also minimizing any potential trade-offs from the elimination of specific kinds of agricultural support. A scenario whereby all global agricultural support were to be removed by 2030, without being repurposed, would result in a 1.3 percent decrease in crop production and a 0.2 percent decrease in livestock production. Global farm employment would fall by 1.3 percent, and further still by 2.7 percent in emerging economies (BRIC countries). Eliminating border measures alone would increase crop and livestock production. However, this would also result in a shift towards more confined feeding operations, with less deforestation and land conversion for pasture, and an associated drop in global GHG emissions of 55.7 million tonnes CO2 e by 2030. The impact on healthy diets is mixed, while the number of people undernourished would drop by 0.2 percentage points. Removing fiscal subsidies alone would reduce global agricultural production and result in less use of inputs and land (cropland and pasture), helping to preserve nature and cutting emissions by an estimated 11.3 million tonnes CO2 e by 2030. However, this would likely increase diet costs and hurt farm incomes for consumers in developed and developing countries, especially female-headed households and poorer households dependent on subsidies. Because agricultural support is often based on production or inputs, such as area planted or number of livestock, support is unevenly distributed across the agriculture sector, with large farms being the major beneficiaries. When repurposing and reforming agricultural support, policymakers should ensure greater equity and access for all producers.